Investigating the Kinetic Effect on Structural Evolution of LixNi0.8Co0.15Al0.05O2 Cathode Materials during the Initial Charge/Discharge - Jo, Eunmi; Hwang, Sooyeon; Kim, Seung Min; Chang, Wonyoung (AMER CHEMICAL SOC, 2017)
In this work, we investigate the structural evolution and reaction kinetics of LixNi0.8Co0.15Al0.05O2. (NCA) cathode materials induced by the initial charge/ discharge as a function of the state of charge (SOC SO and 90%) and C-rates (0.1-10C), with a combination of high resolution transmission electron microscopy (HRTEM) imaging, selected area electron diffraction (SAED), and electron energy loss spectroscopy (EELS). During initial charging, the effects of C-rates on the structural modifications of NCA cathode materials are strongly dependent on how much the lithium is extracted from the pristine NCA. The structural modifications become more substantial as the extent of the charge increases, particularly at higher C-rates. In the highly delithiated state (90% SOC), even the particles charged at the same C-rate show significant variations in the degree of the structural modifications. The changes in the crystallographic and electronic structures at the subsurface scales, which were induced by the initial charging to 90% SOC at the rate of 0.1C, are nearly recovered during the initial discharge, except for the NCA discharged at the rate of 10C. To quantify the extent of the irreversible phase transition at the nanoscale, we have utilized HRTEM imaging and scanning transmission electron microscopy (STEM) EELS line scanning techniques, which enable us to draw complementary results. This comparative analysis provides valuable information that is useful not only for obtaining a complete understanding of the mechanisms by which the degradation is initiated, but also for improving and designing Ni-rich layered cathode materials with better charging and discharging kinetics.
Keywords: X-RAY-DIFFRACTION; CAPACITY-FADING MECHANISMS; ELECTRON-MICROSCOPY; SURFACE-STRUCTURE; ION; LINI0.8CO0.2O2; DEGRADATION; ABSORPTION; PARTICLES; BATTERIES